Life Skills for Personal and Professional Development of the Teachers - Tiwari, Poonam; Bajpai, Anjali (THE PRIMARY TEACHER, 2018)
Teachers hold the key to secure our future as they are invisible hands that mould and shape our society. Modern society demands high quality teaching and learning from teachers. Their activities in the classroom will impact the wellbeing of the economy and success of the society. Teachers play a major part in shaping the values, knowledge and skills of the students. Teachers have to possess a great deal of knowledge and skill with regard to both teaching and assessment practices in order to meet the demands and standards of quality education. It will be only possible when the teacher possesses sound physical and mental health. Life Skills would play a significant role in achieving sound status of mind for the teachers, therefore, the need for Life Skills Education is felt for the teachers. By adopting Life Skills,they become aware about these skills and can not only improve the status of their mental health and ensure their wellness, but also transfer this knowledge to their students during their teaching-learning which is important as it has not been made a part of the curriculum of all boards except CBSE. This paper explores the need of Life Skills for the teachers, its importance, about training programmes and courses enhancing life skills for professional and personal development of the teachers. The paper also highlight some examples showing how a teacher can integrate Life Skills Education in the classroom teaching